Pathogenicity and host specificity of Phytophthora palmivora, the causal agent of black pod disease of cocoa / Siti Aisyah Sahalan - Sahalan, Siti Aisyah (Faculty of Plantation and Agrotechnology, 2018)
Cocoa, Theobroma cacao L. is one of the most important industrial crops cultivated in Malaysia. Cocoa has been infected by many fungal diseases; one of them is black pod. Black pod disease had become one of the major diseases in cocoa in Malaysia. It caused by fungal pathogen known as Phytophthora palmivora. The infection on cocoa pods causes brown to black spot on the pod and the spots could spreads rapidly across the outer surface, covering the entire pod with black lesions in just few days. The aims of this study are to determine the disease severity level and host range of P. palmivora associatedwith cocoa black pod. The samples were collected from two locations which are from Kg Chabau, Melaka and Malaysia Cocoa Board, Hilir Perak. The isolate were identified using morphological characteristic. For pathogenicity test, the inoculation study was conducted on cocoa, banana and papaya. Based on pathogenicity test, P. palmivora is highly virulence on cocoa but avirulence on banana and papaya. This study revealed that P. palmivora is host specific pathogen of cocoa.